Application of Focused Group Interviews in Research on Occupational Burnout - Olejnik, Iwona; Michalak, Sylwia (Zastosowanie zogniskowanych wywiadów grupowych w badaniach nad wypaleniem zawodowym, 2024)
Aim: The aim of this article is to highlight the possibilities and limitations of using focus group interviews in studies on professional burnout. Methodology: The study draws on relevant literature and presents findings from original research conducted with four groups of members of Generation Z. Results: Analysis of qualitative research methodologies used in studies on professional burnout indicates that individual and group in-depth interviews are the dominant techniques. The primary goals of these studies are to identify professional experiences contributing to burnout, determine factors leading to stress and burnout, and develop intervention methods in this area. Implications and recommendations: The article offers recommendations for the use of qualitative research methodologies, particularly focus group interviews, in projects related to profession Originality/value: This article presents a novel approach that examines the potential of using focus group interviews to address the sensitive issue of burnout syndrome. The value of this approach is to point out its potential to include the perspective of Generation Z.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 4, s. 61-74
Keywords: qualitative research; focus group interview; professional burnout; badania jakościowe; zogniskowane wywiady grupowe; syndrom wypalenia zawodowego